The Case Con generation, 1970–75. (31st March 2018) - Feldon, Peter; de Chenu, Linda; Weinstein, Jeremy
Abstract : 'Case Con' was an organisation and a magazine for 'revolutionary social work/workers' that, in the 1970s, represented a radical challenge to social work at a time of great change both within the profession and the wider world. This contribution consists of three people who were activists and members of the Editorial Collective and were on a panel for a meeting of the Social Work History Network. Each goes back to their experiences and the documents of the period to elaborate the various themes as they developed and to discuss the impact of their involvement on them, both personally and politically.